Age of diagnosis with endometriosis and potential predicting factors: A single-center cross-sectional study - Soha Wahab; Zeina Chehade; Dima El Oueichak; Miguel Luna Russo; Miran A. Jaffa (PLoS ONE, 2026)
Objective To evaluate the behavioral and clinical characteristics of endometriosis patients at the largest tertiary healthcare center in Lebanon and to analyze the effect of endometriosis symptoms, age of menarche, sexual activity, and infertility on the age of diagnosis with endometriosis. Design Retrospective cross-sectional study of patients who presented to a tertiary healthcare center over 1 year (2018–2019) and were diagnosed with endometriosis ( N = 688 ). Methods A symptom severity score (SSS) ranging from 0 to 3 was employed to estimate the severity of symptoms, specifically focusing on chronic pelvic pain (CPP), dyspareunia, and neuropathic pain. We performed one-way analysis of variance ( ANOVA ), followed by Post Hoc analysis for multiple comparisons using the Least Significant Difference ( LSD ) method to determine the difference in age at diagnosis between groups presenting with different SSS values. We then conducted a multiple linear regression analysis to model the age of diagnosis with endometriosis as a function of severity of symptoms while adjusting for age of menarche, sexual activity, and infertility. Results The mean age of diagnosis was 29.67 years, and the mean duration of follow-up was 4.74 years. The most common symptom was dysmenorrhea (75.7%). One-way analysis of variance (ANOVA) demonstrated a significant difference in the age of diagnosis among patients with different SSS values ( p = 0.006 ). In the multiple linear regression analysis model, the age at diagnosis was earlier for patients with more severe symptoms compared to none, yet significance was present for SSS = 1 (p ≤ 0.001) and SSS = 2 (p = 0.01) , not for patients with the most severe presentation having SSS = 3 (p = 0.23) . This analysis further revealed that infertile patients had an earlier diagnosis of 2.72 years on average compared to fertile patients (p ≤ 0.001). Furthermore, age of menarche didn’t have a significant effect on the age of diagnosis (p = 0.73). Conclusion Our results suggest that the severity of pain symptoms is not always indicative of an earlier diagnosis, which underscores the crucial need to enhance awareness regarding the clinical presentation of this condition in both society and the medical field.